Cost-effectiveness analysis of coronary artery disease screening in HIV-infected men. (29th August 2020) - Nolte, Julia EH; Neumann, Till; Manne, Jennifer M; Lo, Janet; Neumann, Anja; Mostardt, Sarah; Abbara, Suhny; Hoffmann, Udo; Brady, Thomas J; Wasem, Juergen; Grinspoon, Steven K; Gazelle, G Scott; et al.
Abstract: Background: HIV-infected patients are at increased risk of coronary artery disease (CAD). We evaluated the cost-effectiveness of cardiac screening for HIV-positive men at intermediate or greater CAD risk. Design: We developed a lifetime microsimulation model of CAD incidence and progression in HIV-infected men. Methods: Input parameters were derived from two HIV cohort studies and the literature. We compared no CAD screening with stress testing and coronary computed tomography angiography (CCTA)-based strategies. Patients with test results indicating 3-vessel/left main CAD underwent invasive coronary angiography (ICA) and received coronary artery bypass graft surgery. In the stress testing + medication and CCTA + medication strategies, patients with 1–2-vessel CAD results received lifetime medical treatment without further diagnostics whereas in the stress testing + intervention and CCTA + intervention strategies, patients with these results underwent ICA and received percutaneous coronary intervention. Results: Compared to no screening, the stress testing + medication, stress testing + intervention, CCTA + medication, and CCTA + intervention strategies resulted in 14, 11, 19, and 14 quality-adjusted life days per patient and incremental cost-effectiveness ratios of 49, 261, 57, 817, 34, 887 and 56, 518 Euros per quality-adjusted life year (QALY), respectively. Screening only at higher CAD risk thresholds was more cost-effective. Repeated screening was clinically beneficial compared to one-time screening, but only stress testing + medication every 5 years remained cost-effective. At a willingness-to-pay threshold of 83, 000 €/QALY (∼100, 000 US$/QALY), implementing any CAD screening was cost-effective with a probability of 75–95%. Conclusions: Screening HIV-positive men for CAD would be clinically beneficial and comes at a cost-effectiveness ratio comparable to other accepted interventions in HIV care.